THE PRELIMINARY ADSORPTION INVESTIGATION OF URTICA DIOICA L. BIOMASS MATERIAL AS A POTENTIAL BIOSORBENT FOR HEAVY METAL IONS - DIMITRIJEVIĆ, Vladimir D.; STANKOVIĆ, Maja N.; ĐORĐEVIĆ, Dragan M.; KRSTIĆ, Ivan M.; NIKOLIĆ, Milica G.; BOJIĆ, Aleksandar L.J.; KRSTIĆ, Nenad S. (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The removal of Cu(II) ions from aqueous solutions by adsorption onto nettle after incomplete incineration (IIN) has been studied in batch mode. The experimental isotherm results have been fitted using Langmuir, Freundlich, Temkin and Dubinin-Radushkevich equations. A comparison of kinetic models applied to the adsorption of Cu(II) ions on the adsorbent was evaluated for the pseudo-first order, the pseudo-second order and Elovich kinetic models. The pseudo-second order kinetic model was found to correlate the experimental data well. To evaluate competitive adsorption the batch experiments were carried out among the Cu(II), Pb(II) and Cd(II). The affinity order for the ternary system was Pb(II) > Cu(II) > Cd(II). FTIR and SEM analysis indicated that IIN could be used as an efficient biosorbent whose chemical structure and morphology is not altered during adsorption process.